The Use Of Vegetable Oil In Lubricant As Base Oil: a Review - Abdulbari, Hayder A. (2009)
This paper is a review of vegetable oil in lubricant industry. Vegetable oils already used as lubricant since ancient time. The suitability of vegetable oils as lubricant is mainly influenced of its composition and stabilization towards oxidation. The addition of suitable anti-oxidant is believed significantly enhanced the stability of vegetables oil. Therefore the modification of vegetable oil structure is necessary to enhance its performance as a better lubricant.